HUBUNGAN PENGETAHUAN IBU TENTANG GIZI DENGAN STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS WATAMPONE: HUBUNGAN PENGETAHUAN IBU TENTANG GIZI DENGAN STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS WATAMPONE - Mustar (Jurnal Suara Kesehatan, 2022)
Abstract. Because the mother is the one who has the most bond to the kid, the mother's degree of awareness about toddler nutrition has a significant impact on the nutritional health of the toddler. Mothers spend more time with their children than other family members, allowing them to better grasp all of their children's requirements. The expertise of mothers is the most important factor in satisfying the dietary needs of toddlers. To determine the association between a mother's nutritional knowledge and the nutritional status of her children under the age of five. The Cross Sectional approach is a research to study the dynamics of the correlation between risk factors and effects, by approaching, observing or collecting data all at once (point time approach). Analytical survey is research that explores how and why this health phenomenon occurs.The results showed that there was a relationship between maternal knowledge about nutrition and good nutritional status in the Work Area of the Watampone Health Center with the chi square test results obtained p-value = 0.001 p <0.05, there was a relationship between maternal knowledge about nutrition and nutritional status at risk over nutrition in the Watampone Health Center Work Area with the results of the chi square test, p-value = 0.001 p < 0.05 and there is a relationship between mother's knowledge about nutrition and the nutritional status of toddlers in the Watampone Health Center Work Area with the chi square test results obtained p- value = 0.001 p < 0.5 Abstrak. Karena ibu adalah orang yang paling memiliki ikatan dengan anak, maka tingkat kesadaran ibu tentang gizi balita berdampak signifikan terhadap kesehatan gizi balita. Ibu menghabiskan lebih banyak waktu dengan anak-anak mereka daripada anggota keluarga lainnya, memungkinkan mereka untuk lebih memahami semua kebutuhan anak-anak mereka. Keahlian ibu merupakan faktor terpenting dalam memenuhi kebutuhan gizi balita. Tujuan dari penelitian ini adalah Untuk mengetahui hubungan pengetahuan gizi ibu dengan status gizi balita. Penelitian cross-sectional melibatkan pendekatan, pengamatan, atau pengumpulan data sekaligus untuk menemukan dinamika hubungan antara faktor risiko dan konsekuensi (Approach). Analisisi data pada penelitian ini menggunakan survey analitik. Hasil penelitian menunjukkan ada hubungan antara pengetahuan ibu tentang gizi dengan status gizi baik di Wilayah Kerja Puskesmas Watampone dengan hasil uji chi square test didapatkan p-value = 0,001 p < 0,05, ada hubungan antara pengetahuan ibu tentang gizi dengan status gizi beresiko gizi lebih di Wilayah Kerja Puskesmas Watampone dengan hasil uji chi square test didapatkan p-value = 0,001 p < 0,05 dan ada hubungan antara pengetahuan ibu tentang gizi dengan status gizi balita di Wilayah Kerja Puskesmas Watampone dengan hasil uji chi square test didapatkan p-value = 0,001 p < 0,5